Effect of Annealing Temperature on the Structural Characteristics of(Sb203) Compound. - Abd AI- Razak, . A. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The crystal structure and unit cell dimensions of the (S03) compound have been determined by employing the principles of crystallography. The X-Ray diffraction spectra of (Sb203) which recorded as a function of different annealing temperatures (100,150,200 and 250)Â±5c and for durations (0.5 hr, 0 1hr, l.Shr and 2hr), showed a noticeable improvement, a decreasing in the unit cell dimensions and an increasing in the number of diffraction spectra. Indexing of diffraction spectra and refinement of unit cell dimensions showed that the compound (Sb203) which is a cubic system are (a=ll.271A) before annealing, and (a= ll.207A) after annealing at 250Â±5c for (2hr).